2016
DOI: 10.4187/respcare.04479
|View full text |Cite
|
Sign up to set email alerts
|

Sinopulmonary Complications in Subjects With Primary Immunodeficiency

Abstract: BACKGROUND: The aim of this work was to describe the frequency and spectrum of sinopulmonary complications among subjects with primary immunodeficiency disorders. METHODS: The subjects included all patients with primary immunodeficiency who were registered prospectively between January 2004 and December 2013 in the Kuwait National Primary Immunodeficiency Disorders Registry. RESULTS: A total of 202 subjects were registered during the study period. Subjects with combined immunodeficiencies were the most prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Other studies have also reported a high rate of otitis media in XLA patients [31][32][33][34]. In one study, we demonstrated that 81.1% of XLA patients manifested acute otitis media.…”
Section: Otitis Mediamentioning
confidence: 88%
See 1 more Smart Citation
“…Other studies have also reported a high rate of otitis media in XLA patients [31][32][33][34]. In one study, we demonstrated that 81.1% of XLA patients manifested acute otitis media.…”
Section: Otitis Mediamentioning
confidence: 88%
“…Yarmohammadi et al [15] reported a high rate of otitis media in patients with PID (81 of 113 patients, 71.6%), which was significantly higher than in patients without immune defects. Owayed and Al-Herz [31] found the rate of otitis media to be lower (59 of 202 patients, 29.2%). In the third report of the Iranian registry, we reported 46 cases in 731 patients (6.3%) in whom the first presentation of PID was otitis media [3].…”
Section: Otitis Mediamentioning
confidence: 99%
“…In Turkey, the prevalence of PJP among AIDS/HIV patients ranged from 10 to 46.7% [104][105][106], while in Iran, PJP ranged from 4.5 to 39.3% [107][108][109]. Regarding the Arabian Peninsula region, PJP occurring in 9 episodes among primary immunodeficiency disorder patients in Kuwait [110] was found in 5.1% of PJP Pneumocystis jirovecii pneumonia, HIV human immunodeficiency virus, AIDS acquired immunodeficiency syndrome, PCR polymerase chain reaction, BAL bronchoalveolar lavage, CMV cytomegalovirus, CT computerized tomography, y years total HIV-infected patients in Bahrain [111], while accounted for 25% of opportunistic infections in HIV/AIDS patients in Oman with no mortality reported due to this infection [97]. Concerning North Africa, a retrospective analysis in 2013 conducted on HIV-related hospitalizations showed that PJP was responsible for 8.8% respiratory diseases in Libya [112] and accounted for 11.1% death in HIV-infected patients in Tunisia [100].…”
Section: Pneumocystis Pneumoniamentioning
confidence: 99%
“…Pediatric pulmonologists should consider PID as an important component for differential diagnosis in order to enable early recognition and improve outcomes. Pulmonary manifestations of PID can be divided into two main groups―infections and noninfectious complications―which differ from recurrent infections affecting various locations and opportunistic or unusual pathogenic infections to malignancy and lymphoproliferative disorders . Findings of PID on imaging range from consolidation, abscess, and empyema to bronchiectasis and interstitial lung disease .…”
Section: Monogenic Diseases In Respiratory Medicinementioning
confidence: 99%
“…Patients with pulmonary arteriovenous malformation can present with hemoptysis and cyanosis. 17 20 Findings of PID on imaging range from consolidation, abscess, and empyema to bronchiectasis and interstitial lung disease. 21 The organisms in pulmonary infection differ from defects in immunity-encapsulated organisms are typical pathogens in patients with deficient humoral immunity, and infections by fungal organisms are more typical of cellular immune deficiencies.…”
Section: Hereditary Hemorrhagic Telangiectasia (Hht)mentioning
confidence: 99%